Morphometric Alteration of Intestinal Epithelium of Rats (Rattus norvegicus) Submitted to the Technique of Enteropexy - Queiroz, Genilson Fernandes de; Silva, Taciana de Melo Fernandes; Filgueira, Kilder Dantas; Oliveira, Moacir Franco de; Chaves, Hildita Simea de Andrade; Campos, Giovanna Carla de Oliveira; Oliveira, Gleidson Benevides de; Macêdo, Luã Barbalho de; Pimentel, Muriel Magda Lustosa; Olinda, Robério Gomes; Miglino, Maria Angélica (Acta Scientiae Veterinariae, 2016)
Background: Due to the numerous complications that enteropexy may cause in domestic animals and humans, this study aimed at investigating the microscopic level, the damage generated by this technique in mice, in order to investigate the morphometric changes caused by enteropexy technique in rats. Materials, Methods & Results: Eighteen Wistar rats were submitted to surgical technique of enteropexy. To evaluate intestinal disorders they were euthanized at 30 (Group I), 60 (group II) and 90 (group III) days after the procedure. The animals were perfused with 2.5% glutaraldehyde and 4% paraformaldehyde for the removal of intestinal fragments for analysis in conventional microscopy and scanning electron microscopy. In classical histopathology, group I presented mild lesions with necrosis of the epithelium and infiltration of mononuclear cells. After 60 days, extensive ischemic necrosis area was observed, characterized by the denudation of epithelium cells and cellular debris in the lumen surface and loss of intestinal crypts. After 90 days (group III) lesions were evident and were characterized by strong coagulative necrosis of epithelial cells and intestinal crypts. Under electron microscopy, group I showed early fusion of the adjacent intestinal walls. After 60 days there was adherence of luminal stenosis and intestinal walls. In group III loss of epithelium and substitution of necrotic tissue were identified. Discussion: In the current study it was noticed microscopically that the groups had inflammatory reactions to foreign bodies. It is known that the sutures, independent of manufacture, behave as foreign bodies that induce tissue inflammation of the recipient organism and could harm the scar repair. Among the surgical threads, the nylon type (which was chosen for the current experiment) is indicated in the approach tissues in general and bandages, including cardiovascular, ophthalmic and neurological procedures. This category wire induces minimal inflammation of the receptor tissue. In studies of the histopathological analysis of the tissue reactions produced by the wire implant or nylon thread clamp in rats, it was observed that when the local action of two implants were compared, inflammation showed qualitatively similar responses, although they had different characteristics regarding their course. Inflammation is proportional to the proliferation of fibroblasts and the presence of fibrous tissue around the suture. This quote confirms the analyzed samples, in which, in all postoperative times showed inflammatory process, although at different magnitudes. Surgical research in laboratory animals has expanded in recent decades, mainly due to better anesthetic support, the sophistication of infrastructure, material for perioperative continuous monitoring and an incessant search for species that reproduce human morbid conditions. The main focus of these studies have been improving the knowledge about the pathophysiological mechanisms of disease, undertake therapeutic trials with new drugs, studying biomarkers and evaluate new techniques to be applied prospects in man. The most common sites of occurrence of intestinal are ileocolic intussusception junction and jejunojejunal segment. The enteroplication has been used to reduce the occurrence of intussusception, promoting the adhesion of the adjacent serosa layers of intestinal segments and thereby decreasing intestinal motility, their applicability is reported in humans, dogs and cats. The enteropexy technique causes morphological changes in intestinal epithelium of rats, evidenced in conventional and electron microscopy, progress with the passing of time the procedure.